Socialization about character education that cares for the environment among students at Hosana Private High School, Medan: Sosialisasi Tentang Pendidikan Karakter Peduli Terhadap Lingkungan pada Siswa SMA Swasta Hosana, Medan - Dini Hardiani Has; Sutan Sahala Muda Marpaung; Ratna Sari (Universitas Lancang Kuning, 2024)
Character development for students means working on the nature of the educational cycle and outcomes that lead to the development of students' personalities and honorable ethics in a comprehensive, coordinated and adjusted manner, according to skills guidelines. One of the problems that occurs at the local level and in the school climate is the low interest of the local community (including high school/mama level students) in the waste problem. The method used in this community service activity is the lecture or socialization method, direction and education by researchers to provide information to Hosana Private High School students about the importance of protecting the surrounding environment and the school. From the results of the socialization and presentation about air pollution and concern for the environment, it appeared that students were very enthusiastic about listening to the presentation from the resource person. After the presentation from the resource person, a discussion session was held on these two topics. From the results of the presentation about air pollution by the resource person to students, it shows that students' knowledge about environmental pollution is relatively good, this is obtained from the average test score carried out after the presentation of 78 obtained from 40 students. Hosana Private High School students have used public transportation to reduce air pollution. Some students use public transportation (angkot), accompanied by their parents and cycle, which is an effort to reduce air pollution. Likewise, the behavior of maintaining school cleanliness has been implemented by students. This can be seen when the socialization event is over, students clean the room and tidy up the room that has been used.